Design of Public Library in Medan City with Biophilic Architecture Approach - David Pakpahan; Dr. Wahyuni Zahrah, S.T., M.S (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Libraries as a place where various library materials are collected are established to fulfill visitors' reading interests. However, the condition of public libraries in Indonesia is inadequate and unattractive. One of the things that can be done is to design and provide a library with adequate facilities, with open spaces and attractive visuals, but still in accordance with national library standards. The design of Medan city public library is one of the efforts to support the government in increasing the literacy rate and providing public libraries in Medan that have facilities with national standards. The method of solving design problems used in this design is descriptive method by conducting field surveys, observations, documentation and literature studies and analyzing the site and library users. Data collection is divided into two types, namely primary data and secondary data. This public library is designed with a biophilic architecture approach to address environmental issues around the site. This biophilic architecture provides a picture of the natural atmosphere directly in a space. This can be applied by connecting the design with natural elements, by visually presenting these natural elements, such as an open garden in the building.